2017
DOI: 10.1161/circulationaha.116.022907
|View full text |Cite
|
Sign up to set email alerts
|

Gene Expression Profiling for the Identification and Classification of Antibody-Mediated Heart Rejection

Abstract: Tissue-based measurements of specific pathogenesis-based transcripts reflecting NK burden, endothelial activation, macrophage burden, and interferon-γ effects accurately classify AMR and correlate with degree of injury and disease activity. This study illustrates the clinical potential of a tissue-based analysis of gene transcripts to refine diagnosis of heart transplant rejection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
138
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 149 publications
(143 citation statements)
references
References 72 publications
5
138
0
Order By: Relevance
“…Recent reports have identified the Fc-Receptor CD16 as a major checkpoint that controls inflammatory and vascular cytotoxicity resulting from immune alloreactivity. Our observations come on the heels of the recent evaluation of intragraft mRNA transcripts that suggests that CD16-dependent NK activation pathways are prominent for the development of antibody mediated rejection after heart transplantation 20 . These findings illustrate the clinical potential of the biopsy measurement of CD16 and NK cell transcripts to refine the classification and diagnosis of antibody-mediated rejection.…”
Section: Discussionmentioning
confidence: 75%
“…Recent reports have identified the Fc-Receptor CD16 as a major checkpoint that controls inflammatory and vascular cytotoxicity resulting from immune alloreactivity. Our observations come on the heels of the recent evaluation of intragraft mRNA transcripts that suggests that CD16-dependent NK activation pathways are prominent for the development of antibody mediated rejection after heart transplantation 20 . These findings illustrate the clinical potential of the biopsy measurement of CD16 and NK cell transcripts to refine the classification and diagnosis of antibody-mediated rejection.…”
Section: Discussionmentioning
confidence: 75%
“…The interface between the allograft and its recipient is the thin layer of donor EC lining the walls of the blood vessels supplying nutrients to the allograft. Gene profiling studies of renal [6971] and cardiac biopsies [72] undergoing AMR identified EC activation as a significant contributor to graft pathology. Crosslinking of HLA expressed on the surface of EC by DSA triggers a series of intracellular signaling events and activation of immune responses, which are manifested in the histopathological findings in AMR pathology [73].…”
Section: Mechanisms Of Antibody Mediated Graft Injurymentioning
confidence: 99%
“…Macrophage infiltration is observed in heart [3] and renal [99] AMR and predicts a worse outcome [100]. Neutrophil recruitment is seen in lung transplantation and intragraft natural killer (NK) cells have been identified by molecular microscopy techniques in renal [71] and cardiac biopsies [72] diagnosed with AMR. IgG subclass dictates Fc receptor binding affinity [101, 102], thereby influencing leukocyte recruitment.…”
Section: Mechanisms Of Antibody Mediated Graft Injurymentioning
confidence: 99%
“…Several studies have demonstrated that detection of phosphorylated signaling molecules that are activated downstream of HLA cross-linking, including S6 ribosomal protein and S6 kinase, aids in detection of AMR in cardiac allografts (101,102,148). Sis and colleagues first reported that rejecting renal transplants exhibit increased expression of endothelial-associated transcripts (149,150), a finding that has been further substantiated by the same group in cardiac allografts (124,151). Thus, the "molecular microscope" may enable pathologists to further distinguish AMR from other forms of allograft injury (152), and facilitate a better understanding of intragraft changes during AMR, but the field awaits confirmation of these studies by other laboratories.…”
Section: Microvascular Inflammation and Endothelial Injurymentioning
confidence: 94%